Die verhouding tussen die Heidelbergse Kategismus en die Kort Begrip van Faukelius - met besondere verwysing na die teologiese klemverskuiwings in laasgenoemde - Velthuysen, G. C. (Hervormde teologiese studies, 1989)
The relation between the Heidelberg Catechism and the ‘Kort Begrip’ of Faukelius - with particular emphasis on the theological shift in the latter It is indicated in this article that the theological shift from the point of view of the Heidelberg Catechism to that of the Kort Begrip of Faukelius is the result of three things; The fact that the latter was intended to be an abridged version of th e former, that it had its own peculiar intention and that it became a vessel for the scholastic trend in orthodox theology. Some attention is also given to the possible influence the prolonged use of the Kort Begrip as official handbook for the Catechism, had on the theological thought and practice of the Nederduitsch Hervormde Kerk van Afrika.